A Case Report: Treatment of Anaplasmosis and Ectoparasitic Infestation in Mixed-Breed Golden Retriever Dog - Situmorang, Fernando Jose Immanuel Clinton; Suartha, I Nyoman; Jayanti, Putu Devi (Universitas Airlangga, 2024)
Anaplasmosis is a disease in dogs caused by intracellular gram-negative bacteria belonging to the Anaplasmataceae family. A 6-month-old mixed-breed golden retriever was examined at the Laboratory of Veterinary Internal Medicine, Faculty of Veterinary Medicine, Udayana University, with complaints of itching, tick infestation, weakness, and decreased appetite. The clinical examination revealed pale mucous membranes in the mouth and eye conjunctiva, as well as an infestation of Rhipicephalus ticks on the skin. Routine hematological examination indicated the presence of anemia and thrombocytopenia. Blood smear examination confirmed the presence of Anaplasma sp. Treatment was provided in a causative and supportive manner. Causative therapy involved the administration of doxycycline at a dose of 10 mg/kg body weight orally for twenty-eight days, ivermectin at a dose of 0.2 mg/kg body weight injected subcutaneously every two weeks for four weeks. Supportive therapy included the daily administration of Fufang E'jiao Jiang ®(Dong E Ejiao Co, Ltd., Shandong, China) at 2 ml/day and Sangobion® (PT. Merck Tbk, Jakarta, Indonesia) at one tablet per day for fourteen days. Treatment with doxycycline, ivermectin, Fufang E'jiao Jiang® (Dong E Ejiao Co, Ltd., Shandong, China), and Sangobion® (PT. Merck Tbk, Jakarta, Indonesia) resulted in a positive outcome for the dog, with improved activity, hair growth, good appetite, and the absence of ticks.